(untitled) - FAO (Rome, 1995)
The book includes: reviews of tuna fisheries interactions and research on the interactions, including methods for their study; new methods for studying tuna fisheries interactions and examination for their applicability; case-studies on tuna fisheries interactions; analyses of tuna fisheries involved in interactions and their management
Keywords: aquaculture